Loading...

The answer to the problem of 12X plus 13 equals 9 is x equals -1/3.

1 and 3

6

No solution. Multiply second equation by 3 and get 12x + 6y = 0 but already stated 12x + 6y = 9...

12x + 9 = 10x + 1 Subtract 10x from both sides: 2x + 9 = 1 Sutract 9 from both sides: 2x = - 8 Divide both sides by 2: x = -4

False12x - 66 = 3x + 912x - 3x = 9 + 669x = 65x = 7.22Check:12(7.22) - 60 + 6 = 1(7.22) + 9 + 2(7.22)86.64 - 66 = 7.22 + 9 + 14.4420.64 = 30.66

3x multiplied by (12x plus 9) is:3x(12x + 9)= (3x * 12x) + (3x * 9)= 36x2 + 27x

(2x + 3)(2x + 3)

It is: 122-4*(9*-2) = 216

It is: 12x+9

108

4x² - 12x + 9 = 5 → 4x² - 12x + 4 = 0 → x² - 3x + 1 = 0 → x = (-(-3) ±√((-3)² - 4×1×1))/(2×1) → x = (3 ±√5)/2 → x = (3 + √5)/2 or x = (3 - √5)/2

4x2 - 12x + 9 = 5; whence, 2x - 3 = ±√5, and 2x = 3 ±√5. Therefore, x = ½ (3 ±√5).

The factorisation is as follows: 4x² + 12x + 9 = (2x + 3)2.

The value of X in the equation 3x 2-12x plus 9 is 1.25.

Factor 2x plus 12x plus 28 is (x - 3)(x - 9)

2x + 12x = 14x then include the -9 so the asnwer is 14x-9.

(x-3)(x-9) = 0

x2 + 12x + 27 = (x + 9)(x + 3)

4 + 4 + 1 = 9

true

3(x + 1)(x + 3)

The answer to 1 over 2x plus 13 equals 9 is x equals -8.

13...... 9 plus 5 equals 14...... 14 minus 1 equals 13

The answer to the problem of 13 equals -4x plus 9 is x equals -1.